Housekeeping System for Suborbital Vehicles - Rodrigues, Geraldo (2024)
The authors acknowledge the support provided by the Research project called Mobilising Agenda: New Space Portugal (Ref. C644936537-00000046, Notice ACC02/CO5-i01/2022), funded by the “Mobilising Agendas for Business Innovation” through the “Recovery and Resilience Programme (PRR)”, by the scholarship within the scope of the project VIRIATO, POCI-01-0247-FEDER-046100 and by Portugal 2020 through the Competitiveness and Internationalisation Operational Programme and the Lisbon Regional Operational Programme and co-financed by “FEDER”; by FCT, through LIP, project UIDB/500007/2020; Geraldo Rodrigues acknowledges the support provided by the scholarship within the scope of the project VIRIATO, POCI-01-0247-FEDER-046100 and LISBOA-01-0247-FEDER-04610, GD/34723/2019, through University of Evora, financed by national funds through “FEDER” and by Portugal 2020 through Programa Operacional Competitividade e Internacionalização. Beltran Arribas acknowledges the scholarship support privided by the Research project called Mobilising Agenda: New Space Portugal (Ref. C644936537-00000046, Notice ACC02/CO5-i01/2022), funded by the funded by the “Mobilising Agendas for Business Innovation” through the “Recovery and Resilience Programme (PRR)” through University of Évora. Publisher Copyright: © 2024 by the authors.